ANALISIS PENERAPAN SISTEM INFORMASI MANAJEMEN DAERAH (SIMDA) KEUANGAN PADA PEMERINTAH DAERAH KECAMATAN NATAR - Yusranda, Yusranda; Khoirina, Siti; Yunindra, Andri Eka; WA, Shinta Merinda (Journal of Accounting Taxing and Auditing (JATA), 2024)
AbstractThis research aims to determine the implementation of the Financial Management Information System Application (SIMDA) in the Natar District Regional Government. The method used in this research is qualitative analysis in the form of primary and secondary data. Data collection techniques through interviews, observation and documentation studies. The general research results show that employees in the Natar District regional government have understood the meaning of managing the Financial SIMDA application and the supporting factors that the Natar District regional government has in implementing Financial SIMDA have run optimally and the quality of information produced from implementing Financial SIMDA is considered sufficient. good, but there are network problems in operating the SIMDA Finance application so it can interfere with employee work when inputting data Keywords: Management Information System Application (SIMDA) AbstrakPenelitian ini bertujuan untuk mengetahui Penerapan Aplikasi Sistem Informasi Manajemen (SIMDA) Keuangan Pada Pemerintah Daerah Kecamatan Natar. Metode yang digunakan dalam penelitian ini adalah analisis kualitatif berupa data primer dan sekunder. Teknik pengumpulan data melalui wawancara, observasi dan studi dokumentasi. Hasil penelitian secara umum pegawai pada pemerintah daerah Kecamatan Natar telah memahami makna tentang pengelolaan aplikasi SIMDA Keuangan dan faktor-faktor pendukung yang dimiliki oleh pemerintah daerah Kecamatan Natar dalam menerapkan SIMDA Keuangan sudah berjalan secara optimal serta kualitas informasi yang dihasilkan dari penerapan SIMDA Keuangan dianggap sudah cukup baik, namun terdapat kendala jaringan dalam mengoperasikan aplikasi SIMDA Keuangan sehingga dapat mengganggu pekerjaan pegawai pada saat melakukan penginputan data. Kata Kunci : Sistem Informasi Manajemen (SIMDA)